Treatment and prognosis analysis of patients with moderate-volume hypertensive basal ganglia haemorrhage using DTI-guided stereotactic puncture-based surgery - Li, Jinhong; Zhou, Hu; Li, Jie; Shu, Junyi; Yang, Shiqiang; Yang, Anqiang (Frontiers in Neurology, 2025)
BackgroundHypertensive basal ganglia haemorrhage (HBGH) is a prevalent critical condition in neurosurgery characterised. Severe neurologic dysfunctional outcome despite systemic treatment. The objective of this study is to examine the impact of stereotactic minimally invasive puncture and drainage utilising DTI on the efficacy and quality of life of patients diagnosed with moderate-volume HBGH.MethodStatistical analysis was performed on variables related to each group and clinical prognosis. The primary outcomes of the study were the Glasgow Outcome Scale (GOS) and Activities of Daily Living (ADL) scores 6 months after treatment commenced. Linear regression analysis was used to evaluate the risk factors influencing these outcomes. Multivariate regression modelling was then used to compare the impact of the different treatment modalities on the primary outcome in the three patient groups. Finally, sensitivity and subgroup analyses were performed to verify the stability of the study findings.ResultsThis retrospective study enrolled 65 patients with moderate-volume basal ganglia haemorrhage following a rigorous screening process. The group was divided into a conservative group, a conventional stereotactic group and a DTI-guided stereotactic group according to the main treatment modality. At 12 h, 48 h, 7 days, and 2 weeks after treatment, the amount of residual hematoma was significantly lower in both surgical groups than in the conservative group (p < 0.001). Both surgical groups had significantly higher ADLs than the conservative group after 6 months of treatment (All p < 0.05). In linear multifactorial regression analysis, the conventional stereotactic group (β = 17.82, p = 0.003) and the DTI-guided stereotactic group (β = 35.33, p < 0.001) had higher ADL scores with statistically significant differences compared with the conservative treatment group.ConclusionIn patients with moderate-volume hypertensive basal ganglia cerebral haemorrhage, those treated with DTI-assisted stereotactic surgery may exhibit superior long-term neurological recovery compared to those managed with medical conservative treatment or conventional stereotactic surgery.